Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Experimental study on macro spray, combustion and emission characteristics of biodiesel and diethyl carbonate blends - L. Zhao; X. Zhu; R. Zhao; J. Tian; D. Qian; Q. Lin (International Journal of Environmental Science and Technology, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Biocontrol of strawberry Botrytis gray mold and prolong the fruit shelf-life by fumigant Trichoderma spp. - Q. S. Fan; H. J. Lin; Y. J. Hu; J. Jin; H. H. Yan; R. Q. Zhang (Biotechnology Letters, 2024)

Characteristics and correlation of soil low-molecular-weight organic acids and nutrients in four plantations in red soil area of south China - Y. M. Ren; Z. J. Hou; T. Su; Z. R. Lin; A. Q. Liu; L. P. Cai (International Journal of Environmental Science and Technology, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

What Promotes the Recovery of Salt Marsh Infauna After Oil Spills? - J. W. Fleeger; M. R. Riggio; I. A. Mendelssohn; Q. Lin; D. R. Deis; D. S. Johnson; K. R. Carman; S. A. Graham; S. Zengel; A. Hou (Estuaries and Coasts, 2019)

Formation and characteristics of the Xiaoba landslide in Fuquan, Guizhou, China - F. Lin; L. Z. Wu; R. Q. Huang; H. Zhang (Landslides, 2018)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Soil Nitrous oxide and Carbon dioxide emissions following incorporation of above- and below-ground biomass of green bean - M. Shaaban; Q. Peng; R. Hu; S. Lin; J. Zhao (International Journal of Environmental Science and Technology, 2016)

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

A Review of the Genus Pielomastax Chang (Orthoptera: Eumastacoidea) from China with Description of a New Species - L L Lin; Z M Zheng; R Yang; S Q Xu (Neotropical Entomology, 2014)

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

Kinetic migration of isothiazolinone biocides from paper packaging to Tenax and Porapak - Q.-B. Lin; T.-J. Wang; H. Song; R.-Z. Wang (Food Additives & Contaminants: Part A, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

The occurrence of the feline “Candidatus Mycoplasma haemominutum” in dog in China confirmed by sequence-based analysis of ribosomal DNA - Q. J. Zhuang; H. J. Zhang; R. Q. Lin; M. F. Sun; X. J. Liang; X. W. Qin; W. J. Pu; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Predicted ATP-binding cassette systems in the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; H. Wang; R. W. Hammond; R. Jomantiene; Q. Liu; S. Lin; B. A. Roe; R. E. Davis (Molecular Genetics and Genomics, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

RFLP mapping of QTLs conferring salt tolerance during germination in an interspecific cross of tomato - M. R. Foolad; F. Q. Chen; G. Y. Lin (Theoretical and Applied Genetics, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)